Evaluating the Health Related Quality of Life (HRQOL) of the General Population amid Covid-19 in Bangladesh: A Cross-sectional Investigation - Rayhan, Istihak; Akter, Khaleda; Obaidullah , Mohammad; Islam, Samia; Al Nahian, Md Adnan (The Jahangirnagar Review, 2024)
The COVID-19 pandemic has profoundly impacted billions worldwide, significantly affecting both physical and mental health. This study attempts to evaluate the health-related quality of life of the general population in Bangladesh amid the pandemic. Conducted during the pandemic’s second phase, a cross-sectional survey collected data from 1810 participants aged 18 to 78 years (mean age: 31 years). The sample composition included 50.55% females, 56.08% urban residents, and 63.43% with post-secondary education. Utilizing the SF-12v2 Bangla questionnaire, the study assessed various factors influencing physical and mental health through multivariate regression analyses. Findings reveal significant correlations between physical health and age, gender, family size, income, COVID-19 exposure, sleep patterns, satisfaction with sleep, regular exercise, and major illnesses. Similarly, mental health correlates with age, gender, family size, income, COVID-19 exposure, sleep satisfaction, smoking, illnesses, and exercise, highlighting the pandemic’s complex effects. Recommendations include promoting regular exercise, enhancing mental health support services, managing chronic diseases effectively, and implementing policies that support economic stability and healthy living environments. Implementing these recommendations is crucial to safeguard public health, promote resilience, and ensure sustained well-being in Bangladesh amidst ongoing and future health challenges. This proactive approach will contribute to building a healthier and more resilient population, capable of effectively navigating and mitigating the impacts of infectious diseases similar to COVID-19.